Understanding gender inequality in a rural African family unit (household): a case study of a village in the Greater Giyani Municipality, Limpopo Province - Mahlaule, Tsakane (My University, 2019)
Despite gender mainstreaming through various legislation and policies geared towards addressing gender inequality in South Africa, discrimination against women remains prevalent in South Africa. Society is not only gendered, it is structured to reflect, reinforce and perpetuate divisions along variables such as customs, race and class. On the whole, it is constructed to create what Ely & Fletcher (2003: 07) refer to as interlocking systems of power. For this reason, there is need for a deeper understanding on how women in rural communities confront the issue of inheritance, especially in a dual legal system as the one they are subjected to in traditional authority-led villages. I argue that historically the VaTsonga communities are not inherently patriarchal. I claim that colonialism and apartheid policies invented traditions that forced these communities to be patriarchally structured for practical reasons. This was achieved in various ways including, land dispossession, codification of African customs into formal customary laws, migrant labour, destruction of the African family structure, and many more. I argue that gender inequality persists in rural families of the VaTsonga people of South Africa due to structural conditions that have since permeated all aspects of public and private life. Wekker (cited in Franken et al. 2009: 73) defines gender as ‘a layered social system that gives meaning to the biological differences between women and men while operating on different levels such as the personal, symbolic and institutional levels.’ These inequalities play out in the home and in institutional spaces. For example, role allocation and the gender division of labour in the household keep women in unpaid labour, while the economic factors which force women’s perpetual dependence on men have far-reaching consequences for especially rural women. Furthermore, distorted customary laws such the Traditional Courts Bill 2012 implied that rural women will have even fewer rights than they had under apartheid. Article 9 of the Constitution demands that ‘custom, culture and religion shall be subject to the equality clause contained therein. Despite the Bill of Rights, in rural areas women are treated like minors with no substantive rights and equality. Often they are denied custodianship of the family unit’s assets and resources including land. Girls are socialized to embrace set feminine roles which prescribe submissiveness and dependence. These traits and manners of existence extend into adulthood with lines drawn between them and men along gender biases and entrenched discrimination. Women are forced by convention to put their goals and needs secondary to those of their male relatives, be it the father, boyfriend, male siblings, husband and so on. It is in this context that the woman is perpetually viewed as a mere subject for the performance and satisfaction of patriarchy.
A research report for submission to the Faculty of Humanities, University of Witwatersrand in fulfilment of the requirements for the degree of Master of Arts in Political Science, Johannesburg 2019
Keywords: Equality; Sex discrimination; Rural development